DIRECTIONS OF FOCUS AND RESOURCES OF AN ENTERPRISE STRATEGIC DEVELOPMENT - RUDNICHENKO, Yevhenii; HAVLOVSKA, Nataliia; BRES, Andryi; ROZDOBUDKO, Ella (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The concept of «personnel management» is considered, taking into account the main scientific approaches and practical aspects of its implementation at enterprises. Based on the generalization of modern scientific views of various authors, the main approaches to the definition of personnel management are distinguished: systemic, process, organizational-economic and human centric. The proposed author's definition covers all these approaches, emphasizing the target orientation, the presence of influence mechanisms, the sequence of managerial actions and the focus on personnel development. Namely, personnel management should be understood as a purposeful system of managerial actions, which includes planning, formation, development and effective use of personnel, is implemented through organizational, economic, social and psychological mechanisms of influence, and is aimed at achieving the strategic and tactical goals of the enterprise and revealing the potential of employees. The relationship between personnel management and types of organizational management structures: linear, functional, linear-functional and matrix is studied. Within the framework of the linear organizational structure, personnel management is integrated into the general management system, and its functions are performed directly by the head of the enterprise or line managers. In the functional structure, personnel management is represented by a separate HR service that performs purely personnel functions and is directly subordinate to the general manager or his deputy. The linear-functional structure combines the advantages of previous models: the HR department interacts with both top management and line managers, performing strategic and operational tasks. The most flexible option is the matrix organizational structure, where personnel management plays the role of coordinator of employee mobility between projects and functional areas. In general, the article substantiates that the effective integration of personnel management into the organizational structure of the enterprise is an important factor in ensuring its competitiveness, labor productivity and innovative development.
Keywords: personnel; personnel management; organizational structure; components of personnel management